Pelatihan Pengemasan dan Labeling Produk untuk Meningkatkan Kemampuan Manajemen Pemasaran Bagi UMKM di Desa Sukaragam - Ayu Amanda Damanik; Etty Zuliawati Zed; Katarina Ija Muda; Ahya Ansori; Tirmansah Tirmansah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This service aims to improve the capabilities of MSMEs through packaging and labeling training. Apart from that, the aim of this training is to provide MSME players with an understanding of the importance of attractive and informative packaging and labels in influencing consumer purchasing decisions. Good packaging not only protects the product, but also functions as a promotional tool that can increase the product's attractiveness in the market. Labeling that complies with standards can also increase product credibility and make it easier for consumers to obtain important information, such as raw materials, expiration date and distribution permits. With this training, it is hoped that MSMEs in Sukaragam Village will be able to implement more effective marketing strategies, increase product competitiveness, and expand market reach..